The Effect of Corporate Social Responsibility, Free Cash Flow and Leverage on Earnings Management with Managerial Ownership as Moderating - Flourien Nurul Chusnah; Aisiyah Pangesti (Lembaga Penelitian Universitas YARSI, 2023)
This study aims to determine the effect of corporate social responsibility, free cash flow and leverage on earnings management with managerial ownership as a moderator in consumer goods industrial companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. This study uses quantitative research methods, which are measured by using multiple linear regression method with Eviews 12 software. The population in this study are consumer goods industrial companies listed on the Indonesia Stock Exchange from 2018 to 2021. Sampling using purposive sampling method with a total sample of as much as 23 companies with a research period of 4 years so that the total observations in this study were 92 observations. The data collection techn ique uses the documentation method through the IDX official website www.idx.co.id. The results of this study prove that (1) corporate social responsibility, free cash flow has a negative effect on earnings management, (2) leverage has no effect on earnings management, (3) managerial ownership is able to moderate the relationship of corporate social responsibility to earnings management, (4) ownership managerial is not able to moderate the relationship of free cash flow and leverage on earnings management.